The comparative analysis of upgrade training systems in Russia and Germany - V P Mikhailova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2009)
The comparative and contrastive studies acquire the pivotal importance in the given context. The urgency of the comparative and contrastive studies is entailed by the indispensability of the search for new forms and methods of specialists' vocational training taking into account the world practice in accordance with the contemporary social and economic background of the Russian society.